2011
DOI: 10.1371/journal.pntd.0001345
|View full text |Cite
|
Sign up to set email alerts
|

Human Cellular Immune Response to the Saliva of Phlebotomus papatasi Is Mediated by IL-10-Producing CD8+ T Cells and Th1-Polarized CD4+ Lymphocytes

Abstract: BackgroundThe saliva of sand flies strongly enhances the infectivity of Leishmania in mice. Additionally, pre-exposure to saliva can protect mice from disease progression probably through the induction of a cellular immune response.Methodology/Principal FindingsWe analysed the cellular immune response against the saliva of Phlebotomus papatasi in humans and defined the phenotypic characteristics and cytokine production pattern of specific lymphocytes by flow cytometry. Additionally, proliferation and IFN-γ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…Similarly to our results, a specific proliferative response to P . papatasi saliva was showed in 30% of a small group of exposed donors in a CL endemic area and no correlation was observed between these responses and proliferation to soluble Leishmania antigens [41]. However, absence of IFN-γ and IL-10 production by T CD8+ cells, in favor a Th2-type cellular response, was observed in this work.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Similarly to our results, a specific proliferative response to P . papatasi saliva was showed in 30% of a small group of exposed donors in a CL endemic area and no correlation was observed between these responses and proliferation to soluble Leishmania antigens [41]. However, absence of IFN-γ and IL-10 production by T CD8+ cells, in favor a Th2-type cellular response, was observed in this work.…”
Section: Discussionmentioning
confidence: 57%
“…It was shown that P . papatasi saliva was able to induce the activation of IL-10 producing T cells in naturally exposed individuals [41]. Although we did not detect any significant IL-10 production in response to SGE, we further analyzed proliferation and IFN-γ production to SGE in the presence of an anti-human IL-10 antibody, in order to determine whether the observed SGE-specific cellular responses are down-regulated.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In similar fashion, MDDCs from Iraq-based military personnel donors bitten by sand flies but not infected with Leishmania induced significantly less cellular proliferation compared with unexposed donors (Figure 5B). A recent report52 showed that CD4 + T cells from sand fly-exposed humans stimulated with SGS expressed high levels of IFN-γ. When CD8 + T cells from the same donors were stimulated with SGS, high amounts of IL-10 were produced.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the natural immune response to mosquito bites does not afford protection against malaria, and experimental models of mosquito exposure do not demonstrate substantial protection against Plasmodium (Kebaier et al, 2010; Pollock et al, 2011). This may be attributed to several factors, including the quantity of saliva secreted into the host (Abdeladhim et al, 2011), the short duration of a mosquito bite (Kebaier et al, 2010), and/or the relative immunogenicity of specific proteins in the natural milieu of saliva compared with artificial hyper-immunization. In contrast, the A. gambiae SGE antisera, prepared in rabbits using Freund’s adjuvant, elicited robust and diverse responses to numerous proteins in saliva.…”
Section: Discussionmentioning
confidence: 99%